2013
DOI: 10.1177/0268355512473911
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endovenous laser ablation and high ligation and stripping for varicose vein treatment: a meta-analysis

Abstract: EVLA for varicose veins is safe and effective compared with HLS in a two-year range. More randomized controlled studies follow-up results are needed to clarify long-term recurrence (5 years).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 42 publications
1
35
0
3
Order By: Relevance
“…However, most of these published studies agree that EVLA procedure involves minimal discomfort with fewer complications as compared to surgery. [13][14][15][16] The review of historical evolution of EVLA indicates that the studies in this field were conducted to improve the effectiveness of EVLA causing minimal patient discomfort with fewer complications and side effects. In this regard, longer laser wavelengths are generally preferred in EVLA.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these published studies agree that EVLA procedure involves minimal discomfort with fewer complications as compared to surgery. [13][14][15][16] The review of historical evolution of EVLA indicates that the studies in this field were conducted to improve the effectiveness of EVLA causing minimal patient discomfort with fewer complications and side effects. In this regard, longer laser wavelengths are generally preferred in EVLA.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive techniques with the use of lasers, sclerotherapy, and radiofrequency ablation have transformed varicose vein treatment from a highly morbid surgery into a minimally invasive outpatient procedure (114). In a large meta-analysis of 1,128 limbs treated with endovenous laser ablation (115), the infectious adverse event rate was 0.33%, notably lower than the rate of 1.91% associated with surgical ligation and stripping. Although the routine use of antibiotic prophylaxis is not indicated, adherence to sterile technique remains paramount (116).…”
Section: Lower-extremity Superficial Venous Insufficiency Treatmentmentioning
confidence: 99%
“…17 Surgical intervention has been reported by some studies to have lower long-term recurrence rates, but a meta-analysis by Pan et al showed no significant difference compared with endovenous ablation by 2-or 5-year follow-up. 18 Surgical intervention tends to be reserved for patients with a large dilated and tortuous saphenous vein that is directly under the skin. 19 Recent studies comparing endovascular treatments to surgical stripping have had difficulties recruiting patients to randomization as patients do not desire to be in the surgical arm.…”
Section: Surgical Venous Strippingmentioning
confidence: 99%